The traditional Barong Tagalog embroidery - Miranda, Joan Marriel Mangahas
Philippine embroidery in Barong Tagalog has drawn inspirations from cultural minorities and foreign influences. It distinguishes the garment from that of other countries because of the combination of methods and the intricacy utilized in the construction. Through the course of time, embroiderers have taken innovations in the making of the motifs of the Barong Tagalog. The embroiderers skillfully combine them with innovations on techniques and designs in order to produce designs that are distinctly Filipino made. Thus, the establishment of the Filipino trademark such as Barong Tagalog embroidery proved to be beneficial in the enrichment of the Filipino culture and economic growth. By using the visual notation method in tracing the patterns and the designs of the embroidery motifs, the researcher was able to study the Philippine embroidery motifs on Barong Tagalog during the Spanish era and the twenty-first century. Also, the researcher was able to describe the use of motifs and the methods of application on the Barong Tagalog. Moreover, purposive sampling method was used in selecting the interviewees from the centers of Philippine embroidery such as Pandi, Bulacan and Taal, Batangas. Furthermore, key employees from the embroidery factories such as Milk Mary and Bay View were interviewed in order to define the current methods and patterns used in the twenty-first century while relating it to the motifs utilized during the Spanish era. The twenty-first century embroidery motifs on the Barong Tagalog were the result of the imposition of arts, culture and religion of the Spanish. Moreover, the designs, method of application and selection of colors of threads in the twenty-first century Barong Tagalog can be depicted in the Spanish era. Since the topic has not been fully explored, the researcher hopes to enlighten the readers on the said subject and develop their interest on the great Filipino skill - the art of embroidery.